2020
DOI: 10.3389/fphar.2020.00116
|View full text |Cite
|
Sign up to set email alerts
|

Escins Isolated from Aesculus chinensis Bge. Promote the Autophagic Degradation of Mutant Huntingtin and Inhibit its Induced Apoptosis in HT22 cells

Abstract: The pathogenesis of Huntington's disease (HD), an inherited progressive neurodegenerative disease, is highly associated with the cytotoxicity-inducing mutant huntingtin (mHtt) protein. Emerging evidence indicates that autophagy plays a pivotal role in degrading aggregated proteins such as mHtt to enhance neuronal viability. In this study, by employing preparative high-performance liquid chromatography (pre-HPLC), ultra-high performance liquid chromatography diode-array-detector quadrupole time-of-flight mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Aescin is a mixture of chemically related triterpenic glycosides. It is widely present in the seeds of virtually all Aesculus species: A. assamica [34][35][36], A. californica [37], A. chinensis [38,39], A. glabra [40], A. hippocastanum [41,42], A. indica [41], A. pavia [43,44] and A. turbinata [45,46]. Aescin content, in terms of compound profile and quantity, varies among the Aesculus species [44,47].…”
Section: Medicinal Uses Of Aesculus Spmentioning
confidence: 99%
See 2 more Smart Citations
“…Aescin is a mixture of chemically related triterpenic glycosides. It is widely present in the seeds of virtually all Aesculus species: A. assamica [34][35][36], A. californica [37], A. chinensis [38,39], A. glabra [40], A. hippocastanum [41,42], A. indica [41], A. pavia [43,44] and A. turbinata [45,46]. Aescin content, in terms of compound profile and quantity, varies among the Aesculus species [44,47].…”
Section: Medicinal Uses Of Aesculus Spmentioning
confidence: 99%
“…Many biological activities of aescin validate the traditional use of seed extracts. Aescin exhibits potent anti-inflammatory [31,32,48,49], anticancer [44,[50][51][52], antiviral [46,[53][54][55], antifungal [35], antidiabetic [34,45,48], antiedema [32], antioxidative [49,56,57] and anti-apoptotic [39] effects. Aescin is a promising phytochemical for anticancer drug development [50], as well as for the treatment of neurodegenerative diseases [39], neuropathy [58] and diabetic nephropathy [59].…”
Section: Medicinal Uses Of Aesculus Spmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidences suggest that the neurobiological function of aescin is related to the Akt and mammalian target of rapamycin (mTOR) signaling pathway [ 14 , 15 ]. For instance, aescin protected retinal pigment epithelium cells from oxidative stress via activating the Akt signaling pathway [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, aescin protected retinal pigment epithelium cells from oxidative stress via activating the Akt signaling pathway [ 16 ]. In Huntington's disease, it promoted neurodegeneration through mTOR signaling pathways [ 15 ]. Our previous studies found that the mTOR signaling pathway played an important role in the protection against brain I/R injury both in vitro and in vivo [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%